Aspirin Prophylaxis for the Prevention of Thrombosis: Expectations and Limitations. (7th February 2012) - Rao, Gundu H. R.; Fareed, Jawad
Abstract : Platelets play a very important role in the pathogenesis of acute vascular events leading to thrombosis of the coronary and cerebral arteries. Blockage of these arteries leading to regional ischemia of heart and brain tissues precipitate heart attacks and stroke. Acetyl salicylic acid (Aspirin) has been the drug of choice for over half a century for the primary and secondary prophylaxis of thrombotic events. In spite of its extensive use as an antiplatelet drug for the prevention of vascular thrombosis, there is considerable concern about the degree of protection it offers, to patients under aspirin therapy. In this paper, we explain the phenomenon of aspirin resistance, discuss the limitations of aspirin therapy, and suggest methods to monitor "at-risk" individuals. Ability to monitor and determine at risk patients will provide opportunities for the clinicians to customize antiplatelet therapies.